(untitled) (Revista Angelus Novus, 2016)
This article focuses on the musical culture of Porto Alegre in the first decades of the twentieth century. For that it analyzes the formation of the Municipal Band of Porto Alegre, an institution that was created and funded by the government (bearing including the name of the city), emphasizing the relationship between population, their artistic activities and their identity desired. The band will take place in the dialogue between educated elite, the government and sectors of afro-descendant community, ahead of the tensions resulting from the processing of this musical ensemble. The analysis of this musical institution aims to realize what were the terms of this debate and how was articulated the relationship between music and people.